"Each Creature, Resplendently Transfigured": Development of Teaching in Laudato Si'. (June 2018) - O'Halloran, Nathan W.
Three stages can be traced in the Catholic Church's magisterial teaching on the status of nonhuman creatures in the eschatological New Creation. In this article I ask three questions: which, why, and how: Which creatures are in the new creation, why are they part of the New Creation, and how will they be there? I argue that Laudato Si' gives a new magisterial answer to these three questions and constitutes an important new development in the teaching on New Creation.